Physicians' Role in Helping to Die - Guerrero Quiñones, Jose Luis (Conatus - Journal of Philosophy, 2022)
Euthanasia and the duty to die have both been thoroughly discussed in the field of bioethics as morally justifiable practices within medical healthcare contexts. The existence of a narrow connection between both could also be established, for people having a duty to die should be allowed to actively hasten their death by the active means offered by euthanasia. Choosing the right time to end one’s own life is a decisive factor to retain autonomy at the end of our lives. However, there is no definitive consensus on why physicians should be the ones performing the medical procedure to end a person’s life. The moral problems arising from such assertion are not to be taken lightly, for medical tradition has long regarded the duty not to kill, not to actively end a patient’s life, as the core moral obligation that gives meaning to the medical profession. Our concern is to question the moral justifiability of the arguments offered by physicians not to actively help patients die.